Respuesta :

Answer:

Option B

Step-by-step explanation:

Option A

a² - b² = (a+ b)(a - b)

It's a polynomial identity.

Option B

a³ + b³ = (a - b)(a² - ab + b²)

It's not a polynomial identity.

Because the identity is,

a³ + b³ = (a + b)(a² - ab + b²)

Option C

a³ - b³ = (a - b)(a² + ab + b²)

It's a polynomial identity.

Option D

(a²+ b²)(c² + d²) = (ac - bd)² + (ad + bc)²

                         = a²c² - 2abcd + b²d² + a²d² + b²c² + 2abcd

                         = a²c² + b²c² + b²d² + a²d²

                         = c²(a² + b²) + d²(a² + b²)

                         = (a²+ b²)(c² + d²)

Therefore, it's a polynomial identity.

Option B will be the answer.